Comparison of Long-Term and Perioperative Outcomes of Robotic Versus Conventional Laparoscopic Gastrectomy for Gastric Cancer: A Systematic Review and Meta-Analysis of PSM and RCT Studies - Feng, Qingbo; Ma, Hexing; Qiu, Jie; Du, Yan; Zhang, Guodong; Li, Ping; Wen, Kunming; Xie, Ming (Frontiers in Oncology, 2021)
Background To investigate perioperative and oncological outcomes of gastric cancer (GC) after robotic versus laparoscopic gastrectomy (RG versus LG), we carried out a meta-analysis of propensity score matching (PSM) studies and randomized controlled study (RCT) to compare the safety and overall effect of RG to LG for patients with GC. Methods PubMed, Web of Science, EMBASE and Cochrane Central Register were searched based on a defined search strategy to identify eligible PSM and RCT studies before July 2021. Data on perioperative and oncological outcomes were subjected to meta-analysis. Results Overall, we identified 19 PSM studies and 1 RCT of RG versus LG enrolling a total of 13446 patients (6173 and 7273 patients underwent RG and LG, respectively). The present meta-analysis revealed nonsignificant differences in tumor size, proximal resection margin distance, distal resection margin distance, abdominal bleeding, ileus, anastomosis site leakage, duodenal stump leakage rate, conversion rate, reoperation, overall survival rate and long-term recurrence-free survival rate between the two groups. Alternatively, compare RG with LG, RG has longer operative time (p=0.04), less blood loss (p <0.0001), earlier time to first flatus (p=0.0003), earlier time to oral intake (p=0.0001), shorter length of stay (p=0.0001), less major complications (p=0.0001), lower overall complications (p =0.0003), more retrieved lymph nodes (P <0.0001) and more cost (p <0.00001). Conclusions In terms of oncological adequacy and safety, RG is a feasible and effective treatment strategy for gastric cancer but take more cost in comparison with LG.